Penal mediation as an alternative of transferred criminal settlement done by children - Rohman Hakim; Basuki Rekso Wibowo; Krisnadi Nasution; Hufron (Technium Social Sciences Journal, 2021)
The type of research in this writing is Normative legal research, namely legal research that focuses on the study or study of legislation in coherent legal system and to sharpen problem analysis. The Legislative Body, in this case the House of Representatives, should immediately revise the Law on the Juvenile Criminal Justice System by including the Article on juvenile criminal cases, the settlement is through the Penal Mediation mechanism and immediately promulgated in the form of a Law. In order to have a binding legal force and become a guideline for law enforcement officers in the General Court environment.